Síntese de novos triazóis, análogos da α e nor-β-lapachona com núcleo selenóide, obtidos via reações “click”, e determinação do potencial antiproliferativo por modulação redox - Lima, Daisy Jereissati Barbosa (2022)
β-lapachone has emerged as one of the most studied quinones with anticancer potential in recent years. Its derivative, Nor-β-lapachone, demonstrates similar activity, inspiring the synthesis of new quinoidal derivatives with similar mechanism and varying potencies. Thus, the objective of this work was to synthesize and characterize molecules based on the structure of α-lapachone, evaluate the cytotoxic potential, relate structure-activity of compounds derived from Nor-β-lapachone and evaluate the mechanism of action involved in the cytotoxicity of the compound most active among those sinthetized, compared to molecules already tested in human tumor cells. Eight molecules similar to α-lapachone were synthesized by means of click reaction with incorporation of groups containing selenium and investigated the effect of these compounds on the viability of several tumor cell lines and a non-tumor cell line, using the MTT assay. Molecules inspired by the quinoidal skeleton of Nor-β-lapachone were also tested in the same cell lineages to study the structure-activity relationship. The molecule ENSJ 670, derived from Nor-β-lapachone, stood out in potency and selectivity among the molecules tested and, therefore, was selected for continuity in the mechanism of action studies. Nor-β-lapachone was used as a positive control to compare potencies and mechanisms of action. The mechanism experiments were performed on the colon cancer cell line HCT-116. The ENSJ 670 molecule showed decreased cell viability, significant generation of reactive oxygen species, high mitochondrial depolarization rate and death evidenced by apoptosis, demonstrating superior performance to the positive control, Nor-β-lapachone. After these findings, the influence of ENSJ670 on the enzyme NQO1 was sugested through the molecular docking assay and interaction of the test molecule with this enzyme was observed to a greater degree than dicumarol, a recognized inhibitor of the same. In a bioenzymatic inhibition assay with dicumarol, where the molecules DY37 and ENSJ 670 were used, they showed potentiated cytotoxic activity. Naphthoquinone ENSJ 670 demonstrates potent antitumor activity in vitro and cell death mechanism associated with mitochondrial action with possible involvement of the NQO1 enzyme; highlighting the importance of other later trials to validate the therapeutic potential of this molecule.